Desorption of Cadmium from Cocoa Waste Using Organic Acids - Sebastián Piedrahíta-Pérez; Juliana Rodríguez-Estrada; Margarita Ramírez-Carmona; Leidy Rendón-Castrillón; Carlos Ocampo-López (Foods)
This study evaluated the desorption of cadmium (Cd) from cocoa waste-derived flour using organic acids. Cocoa pods were collected from Antioquia and Casanare, Colombia, to analyze the geographical Cd content and its distribution within the pod tissues. Acid selection was performed using a multi-criteria decision-making (MCDM) matrix, and Cd desorption was assessed through a full factorial 23 experimental design, considering acid concentration, pulp density, and agitation speed. Additionally, the oxidation–reduction potential (ORP) was monitored as an indicator of the electrochemical dynamics of the process. The results indicated that pods from Casanare exhibited higher Cd concentrations (1.63 ± 0.20 ppm) compared with those from Antioquia (0.87 ± 0.22 ppm), with 49.31% of the metal being accumulated in the pod. Parameters of citric acid at 0.5 M, 5 g/L pulp density, and 120 rpm were found to be optimal for the Cd desorption process, achieving over 95% efficiency. Based on ORP monitoring, a heuristic was proposed to determine the contact time during leaching. This work outlines a scalable process for Cd desorption, adding value to cocoa industry waste for potential applications.